Entomofauna asociada a las fases de descomposición del cadáver de Sus scrofa domestica L. Trujillo, 2015. - Villanueva Villalva, José Carlos (2016)
The work was aimed at determining the cadaverous entomofauna associated to the corpse of Sus scrofa domestica l., the duration of the phases of decomposition, the ecological categorization and insect diversity. It was used a sucker from 3 months of age and 6 Kg of weight, sacrificed by a blow to the heart and exhibited in a cage of 1 x 1 x 0.7 m placed on the campus of the National University of Trujillo located at 8° 06' 58.75" S 79° 02' 72" W to 34 metres above sea level. Temperature and relative humidity were recorded, insects were collected for their determination, and periods of the stages of decomposition were recorded and were assigned to their ecological categories. The Indices of Margalef, Simpson, Shannon Wiener and Pielou were used. The entomofauna found was in the orders Coleoptera, Hymenoptera, Diptera and Dermaptera; in Diptera highlighted the Calliphoridae family and Coleoptera Dermestidae family. Determined 17 families and 32 species that were grouped in: ghouls, necrophilous, omnivores and accidental with abundances of 80, 57%; 17, 45%; 0, 55% and 1, 43%, respectively. The diversity of the cadaverous entomofauna is both low in richness, dominance, and equity. Key words: mortis Entomology, Entomological succession.